Typology of Appearance and "Appearance of Typology" in the Novel "Faserland" by Christian Kracht - Krasilnikov, Roman L. (Respectus Philologicus, 2006)
Literary critics described the novel "Faserland" (1995) by Christian Kracht as a narration about the world of brand goods. The task of the article is to analyze the representation of relation to clothes and the body, reflects practices of modern daily occurrence as a whole. The narrator builds a semiotic system consisting of four parts: clothes, things, outward appearance and smells. He regularly finds such qualitative features a trade mark, colour or material of an object, which allows typifying personality with different criteria. The narrator "envisages" meaningful information for himself and modern culture under the codes: the occupation of a person, his/her participation in a subculture, his place of living, inclination to some trade mark, body practices, and improving his/her appearance. The "cult of typology" gradually becomes the interior, ontological foundation of the text. Now, the basic reader's interest comprises invariable passages from one dress-, look-, thing-, and brand-code to the other.